Pharmacokinetics and safety of an 8 week continuous treatment with once-daily versus twice-daily inhalation of tobramycin in cystic fibrosis patients. (30th November 2015) - van Koningsbruggen-Rietschel, S.; Heuer, H. E.; Merkel, N.; Posselt, H. G.; Staab, D.; Sieder, C.; Ziegler, J.; Krippner, F.; Rietschel, E.
Abstract : This randomized, multicentre, open-label, two-period crossover study showed that inhaling tobramycin either once daily or twice daily for 8 weeks appears to be safe and tolerable for treating patients with cystic fibrosis and chronic P. aeruginosa infection. Abstract: Objectives: We evaluated the pharmacokinetics, safety and tolerability of two different continuous treatment regimens of tobramycin inhalation solution (TIS) in 29 cystic fibrosis (CF) patients chronically infected with Pseudomonas aeruginosa . Patients and methods: In this randomized, multicentre, open-label, two-period crossover study, TIS (300 mg/5 mL) was administered via PARI eFlow ® rapid once daily and twice daily each for 8 weeks. Serum pharmacokinetics of these two regimens was analysed. Tobramycin levels were determined before the morning dose and at 30, 60 and 90 min after the end of nebulization in the middle and at the end of each 8 week cycle. At these timepoints, trough and peak serum tobramycin concentrations ( C max, mg/L) as well as the area under the curve for 0–90 min of tobramycin (AUC0–90min ) were assessed in order to evaluate the risk of systemic toxicity. Safety parameters and forced expiratory volume in 1 s (FEV1 ) were assessed. Results: For once-daily treatment, tobramycin levels were 10% higher after 8 weeks compared with 4 weeks (AUC0–90min ratio = 1.096, 90% CI = 0.860–1.396, P  = 0.5237). For twice-daily treatment, tobramycin levels after 8 weeks showed a 40% decrease compared with 4 weeks (AUC0–90min ratio = 0.608, 90% CI = 0.461–0.802, P  = 0.0055). The AUC0–90min ratio at 8 weeks (once daily versus twice daily) did not differ significantly (AUC0–90min ratio = 0.749, 90% CI = 0.514–1.092, P  = 0.2009). The mean FEV1 did not differ markedly compared between treatment periods or with baseline. No audiological or nephrotoxic side effects were noted. Conclusions: Continuous treatment with TIS (once daily or twice daily) over 8 weeks appears to be safe and tolerable.